Investigation of Health-Related Consequences of Landmine Explosions During the Past 4 Decades (1979-2016): A Retrospective Cross-Sectional Study, Kurdistan, Iran. (19th June 2020) - Fathollahi, Soraya; Yari, Arezoo; Fatemi, Farin; Ardalan, Ali; Bidarpoor, Farzam; Esmailnasab, Nader
ABSTRACT: Objectives: Landmines remain a potential public health concern in the western and southern border regions of Iran. The aim of this study was to assess the health-related consequences of landmine explosions in Kurdistan Province during the past 4 decades. Methods: This retrospective cross-sectional study was conducted in Kurdistan Province of Iran in 2016-2017. The data gathering process was questionnaire based. Survivors, or a member of the deceased's family, were interviewed, and 410 questionnaires were completed. Data analysis was performed by using descriptive or analytical tests in SPSS software V.22. Results: Antipersonnel landmines caused death immediately after the explosion 32.1% of the time, and 67.9% survived with various disabilities, such as blindness, deafness, and limb amputation. Sixty-three percent of the injuries were related to limb amputation, which was the most prevalent injury among survivors. The adjusted regression test revealed a significant relationship between severity of injury and variables such as living in the villages, education, and occupation ( P -value < 0.05). Conclusions: Recognizing the mined areas and intensifying clearance measures are crucial for Kurdistan Province. Providing landmine awareness programs is likely to yield useful results in reducing casualties. Also, landmine survivors should have access to physical and social rehabilitation programs.